Screening A Christmas Carol (Dickens, 1843): Adaptation as Completion - Florent Christol (Cahiers Victoriens et Edouardiens)
This paper investigates cinema and television’s peculiar ‘love story’ with Charles Dickens’s A Christmas Carol (1843). Indeed, the story of Scrooge’s life-changing encounter with the Christmas Spirits has been adapted, revised, condensed, retold, and modernized on screen more than any other work of English or American literature. Why is cinema so attracted to this particular piece? Although the mythic quality of the tale partly explains its persistence over the years, I believe that the interest exerted by the Carol on the film medium has a lot to do with the spectacular apparatus (a series of highly realistic images projected to Scrooge) displayed by the Christmas Spirits to redeem the old miser. For what is the Carol if not a text about a character’s personal cinematic experience? The tale contains ‘techniques’ that would only be developed in cinema, as if Dickens was writing a story to be told by a medium not yet available in the Victorian age. As a consequence, turning the Carol into a movie is to not only ‘adapt’ it in the traditional sense of the word, but to literally complete it (in the sense of achieving what Dickens had started) and fulfill its potential, which may explain the satisfying nature of watching a film adaptation of Carol, regardless of the inner quality of the film itself.